PENGGUNANAN METODE QIRA’ATI DENGAN MEDIA PAPAN FLANEL DALAM PENINGKATAN KEMAMPUAN MEMBACA AKSARA JAWA SISWA KELAS IV SDN 1 PURWOSARI TAHUN AJARAN 2013/2014 - nurrohman, wahid (KALAM CENDEKIA PGSD KEBUMEN, 2017)
Abstract: THE USING OF QIRA?ATI METHODE WITH FLANNEL BOARD MEDIA IN INCREASING OF JAVA CAPITAL READING ABILITY  OF THE 4TH GRADE STUDENT OF STATE ELEMENTARY SCHOOL 1 PURWOSARI  ACADEMIC YEAR 2013/2014. The purpose of this research was: (1) to give a description on  the use of Qira?ati Methode with flannel board media increase the ability of reading the Javanese capital of the 4th grade student of State Elementary School, (2) to see the increase on the ability of reading Javanese (2) to describe the problems and their solutions. This research used Qira?ati methode with flannel board media and implemented in three cycles. The results showed that: the application of Qira?ati methode  can improve ability of reading Javanese 4th Grade Student. Keywords: Qira?ati methode. flannel board  media, reading javanese capital Abstrak: Penggunaan metode Qira?ati dengan media papan flannel dalam peningkatan kemampuan membaca aksara jawa pada siswa kelas IV SDN 1 Purwosari Tahun Ajaran 2013/2014. Tujuan penelitian ini adalah mendeskripsikan penggunaan metode Qira?ati dengan media papan flanel, peningkatan kemampuan membaca aksara jawa dan untuk mendeskripsikan masalah dan solusi. Penelitian ini menggunakan teknik Penelitian Tindakan Kelas dan dilaksanakan dalam tiga siklus. Hasil menunjukkan bahwa: penggunaan metoe Qira?ati dengan media papan flanel dapat meningkatkan kemampuan membaca aksara jawa siswa kelas IV. Kata Kunci: metode Qira?ati, media papan flanel, membaca aksara jawa